sj-tgz-1-las-10.1177_0023830920983591 – Supplemental material for Comparative Analysis of Majority Language Influence on North Sámi Prosody Using WaveNet-Based modeling ... - Hiovain, Katri; Suni, Antti; Kakouros, Sofoklis; Šimko, Juraj (SAGE Journals, 2020)
Supplemental material, sj-tgz-1-las-10.1177_0023830920983591 for Comparative Analysis of Majority Language Influence on North Sámi Prosody Using WaveNet-Based modeling by Katri Hiovain, Antti Suni, Sofoklis Kakouros and Juraj Šimko in Language and Speech ...